2013
DOI: 10.2478/s13382-013-0143-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of construction workers’ hydration status using urine specific gravity

Abstract: Objectives: The study objective was to assess hydration status by measuring USG among construction workers in Iran. Materials and Methods:The study design was comparative and experimental. Sixty participants were randomly selected from the construction workers from a construction campus with a similar type of work, climate and diet and formed 2 groups (individuals exposed to the sun and non-exposed individuals). TWL and USG were measured in both groups on 2 consequent days, at the beginning, mid and end of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 13 publications
1
19
0
1
Order By: Relevance
“…During the last decades, the new insights in the active role of adipose tissue as a metabolic active organ focused the attention on the fat mass component in the evaluation of body health. However, even if this is surely a remarkable aspect, also the FFM content of each individual as an index of health is of growing importance [19,20,28,29], in particular in terms of phase angle (PhA) and BCMI. So, PhA and BCMI have been proposed as other indices capable to describe body composition in terms of fat mass and lean mass in addition to the traditional BMI, to better define metabolic health [18,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the last decades, the new insights in the active role of adipose tissue as a metabolic active organ focused the attention on the fat mass component in the evaluation of body health. However, even if this is surely a remarkable aspect, also the FFM content of each individual as an index of health is of growing importance [19,20,28,29], in particular in terms of phase angle (PhA) and BCMI. So, PhA and BCMI have been proposed as other indices capable to describe body composition in terms of fat mass and lean mass in addition to the traditional BMI, to better define metabolic health [18,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Urine osmolality has been unambiguously associated with insufficient water intake, and it is less invasive, expensive and more sensitive to mild cell dehydration than other indicators [2]. The population has been divided in 2 classes according to hydration status: norm-hydrated subjects with USG <1,020 and dehydrated subjects with USG >1,021 [20]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study (2007) was conducted on workers of surface mines located in Pilbara in Western Australia; and the results obtained from urine samples revealed that 70% of 710 workers were subjected to water scarcity and that 16% of workers needed clinical services (34). Similar conditions were reported for construction workers in Iran (35) and United Arab Emirates (34). Education is important in helping workers maintain their hydration state.…”
Section: Discussionmentioning
confidence: 76%
“…Strategies for developing these interventions have been focused on the process of quantifying heat stress (causes) and strain (consequences). For instance, Bates and Schneider25 ) , Bates et al 27 ) , Miller and Bates28 ) , and Montazer et al 29 ) investigated the hydration status of construction workers and advised that interventions are required to maintain adequate levels of hydration of workers under extreme heat stress conditions. Chan et al 30, 31 ) , Yi and Chan8, 26, 32 ) , Rowlinson and Jia9 ) , and Pérez-Alonso et al 1 ) proposed work and/or recovery thresholds after examining body heat strain limits arising from multiple heat stressors (e.g., meteorology, work and individual characteristics) in the Hong Kong construction industry.…”
Section: Discussionmentioning
confidence: 99%